North aisle - Ghosh, Ayan (2023)
Reverend William Kew Fletcher, arch chaplain at the time, saw an opportunity to restore St. Thomas Church during the economic boom in the wake of the American Civil War (1861-1865). The work was assigned to James Trubshawe, architect to the Government of Bombay, who prepared renovation plans in the traditional Gothic Revival architecture that was popular at the time.